Superior Mesenteric Artery Syndrome Complicated by Gastric Mucosal Necrosis Following Congenital Scoliosis Surgery: A Case Report. Issue 3 (July 2019) - Moyer, Kathleen; Thompson, George H.; Poe-Kochert, Constance; Splawski, Judy
Abstract : Case: This is a report of severe superior mesenteric artery (SMA) syndrome in an 11-year-old girl with congenital scoliosis following posterior spinal fusion and segmental spinal instrumentation. This was complicated by gastric mucosal necrosis but resolved satisfactory with prolonged nasogastric suction, intravenous fluids, and total parental nutrition. Conclusions: All pediatric spine surgeons should be aware of SMA syndrome following spine surgery. This case demonstrates that although rare, significant complications such as gastric mucosal necrosis can occur. When present, it can be treated successfully with prolonged conservative management. Comanagement with pediatric gastroenterology and pediatric general surgery is recommended.